Badiou and Deleuze Read Literature - Lecercle, Jean-Jacques (Plateaus - New Directions in Deleuze Studies : PLAT, 2022)
Considers the 'strong readings' that Alain Badiou and Gilles Deleuze imposed on the texts they readWhy do philosophers read literature? How do they read it? Does their philosophy derive from their reading of literature? If so, to what extent? Anyone who reads contemporary European philosophers has to ask such questions. Lecercle demonstrates that philosophers need literature, as much as literary critics need philosophy: it is an exercise not in the philosophy of literature, where literature is a mere object of analysis, but in philosophy and literature, a heady and unusual mix